[/quote]50/x^2+3x+6 (x^2+3x+6) (6.16) = 6.16(6.16) (x^2+3x+6)[/quote]
Okay, you are multiplying both sides by x^2+ 3x+ 6 to get rid of the fraction but why are you multiplying both sides by 6.16?
No, (6.16)(6.16) is NOT 1! I suppose you meant to divide both sides by 6.1650(6.16)= 1(x^2+3x+6)
And since 50(6.16)= x^2+ 3x+ 6 is not correct, the rest is wrong.308=x^2+3x+6
Then solve using quadratic formula???? Im not sure if this is right.
If you divide both sides by 6.16 you get x^2+ 3x+ 6= 50/6.16= 8.117, approximately so your equation is x^2+ 3x+ 6- 8.117= x^2+ 3x- -2.117= 0 and you can use the quadratic equation to solve that.
Just multiply both sides of 50/(x^2+ 3x+ 6)= 6.16 by x^2+ 3x+ 6 to get
x^2+ 3x+ 6=